(untitled) (Journal of Geography and Environmental Management, 2021)
Today, the number of visitors to national parks grows exponentially every year, hence the anthropogenic load in the mentioned sites increases impacting flora and fauna, as well as other natural resources. To ensure tourism development in all regions, not only popular tourist destinations, creation of maps to ensure development of tourism industry and regulation of tourism activities are important tools, which indicate main tourism resources. User-oriented maps are designed to provide the geospatial information they need primarily for their interests to make geospatial decisions. Well-designed tourist maps may increase the attractiveness of a region and help meeting tourists’ needs. This article presents the process of creating schematic map of routes and infrastructure along Ayusai Gorge for the sustainable development of tourist and recreational activities on the territory of Ile-Alatau National Park using GIS technology. Graphic and attributive data, namely digital raster and vector images, semantic information, the principle of layer-by-layer classification and coding of tourist destinations were used. The raster-vector transformation for data digitization was used within the research and thematic map layers were created on the basis of remote sensing (RS) data, point, linear and polygonal localization objects were digitized. The schematic maps of the routes of the Japanese trail, the Ayusai waterfall trail, the Myn Koz trail and the infrastructure map of Ayusai Gorge were created based on RS data. For the first time, when mapping this territory, satellite images were used and a database of tourist objects was created. The results of this work can be useful in the planning and travelling for consumers, as well as for the creation of a geoinformation database of the national park.